The knowledge [compact disc, unabridged] : a Richard Jury mystery - Grimes, Martha (Grimes, Martha. Richard Jury mystery., 2018)
London's finest and 'the Filth' come together on a double homicide case that involves Kenyan art, rare gems, astrophysics, and a long-fermented act of revenge.